The Effects of Innovative Organizational Climate on Job Performance in Private-sector Employees: Mediating Role of Job Motivation and Self-Efficacy - Niloofar Rezaei; Hassan Shafaei (Journal of Modern Psychology)
Objective: The purpose of this research was to investigate the impact of innovative organizational climate on the job performance of private sector employees, taking into account the mediating role of job motivation and self-efficacy. Methods: A descriptive-correlation approach was employed in the current investigation, utilizing structural equation modeling. The study consisted of 384 employees from the private sector, aged between 21 and 49 years (with a mean age of 35.11±8.17 years), who willingly participated. The research was conducted in Tehran, Iran, in the year 2023. The participants were selected through a convenience sampling method, adhering to the guidelines outlined by Krejci & Morgan. Standard questionnaires were used for data collection. Pearson correlation test and the structural equation modeling were used for data analysis.Results: Results reveled that innovative organizational climate significantly affected job performance (T=6.284). Moreover, innovative organizational climate significantly affected job motivation (T=11.594). Furthermore, innovative organizational climate significantly affected self-efficacy (T=9.509). In addition, job motivation has significantly mediated the relationship between innovative organizational climate and job performance (P<0.001). Finally, self-efficacy has significantly mediated the relationship between innovative organizational climate and job performance (P<0.001). Conclusion: Based on the findings of this research, it is recommended that market holders focus on promoting and enhancing the factors and components that contribute to the innovative organizational climate of private sector employees. Additionally, greater emphasis should be placed on job motivation and self-efficacy of the private sector employees.